Concomitant Central Nervous System Toxoplasmosis and Seronegative Disseminated Coccidioidomycosis in a Newly Diagnosed Acquired Immune Deficiency Syndrome Patient - Michael Valdez MD; Leila Moosavi MD; Arash Heidari MD (SAGE Publishing, 2019)
Opportunistic infections (OIs) are a significant cause of morbidity and mortality in immunosuppressed patients and may be due to bacteria, virus, protozoa, or fungi. Toxoplasmosis is a common cause of central nervous system infection in human immunodeficiency virus (HIV) patients. Coccidioidomycosis is a relatively common fungal infection that may lead to disseminated disease and fungemia in immune-compromised hosts living in endemic regions. This single-patient case report documents the presentation, diagnosis, management, and outcome of concomitant central nervous system toxoplasmosis and diffuse miliary pneumonia with fungemia due to disseminated seronegative Coccidioides immitis in a 33-year-old male patient recently diagnosed with chronic advanced HIV. Impaired cellular immune function, such as defects in the IL-12/IFN-γ pathway or T-helper IL-17-mediated response, is associated with increased severity of coccidioidomycosis. Fungemia and acute respiratory distress syndrome are both associated with very high mortality in coccidioidomycosis. In HIV hosts, negative Coccidioides serology can be seen in up to 25% of cases and therefore other diagnostic modalities should be initiated promptly and simultaneously. This case demonstrates simultaneous OI in the setting of advanced acquired immune deficiency syndrome and emphasizes the need for early diagnosis of HIV and OI in order to ensure prompt initiation of antiretroviral therapy, prophylactic, and therapeutic medications.